El programa “B” de matemática (PBM) (ING) - Buján, Víctor (2003)
In 1995 small groups of parents form eight Costa Rica public schools let the Minister of Education know that they wanted their children to have two more mathematics classes each week, as well as contents beyond those present in the official national mathematics program. The beginning, growth and, finally, the suppression of the so-called “Mathematics Program B” are described.